1975
DOI: 10.1002/ar.1091810104
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal influences on the morphogenesis of the preputial gland of embryonic mice

Abstract: Fetal preputial glands from 14- to 17-day old mouse embryos undergo comparable growth, branching, and display similar degrees of cytodifferentiation when cultured in vitro on medium lacking hormones, on this medium in the presence of either of the fetal gondas, and on medium supplemented with testosterone dipropionate. Conversely, morphogenesis of these analgen is markedly suppressed by estrogen and an anti-androgen, Cyproterone acetate. These observations demonstrate that acquisition of androgen-sensitivity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Later on, the male gland develops faster under the influence of testosterone. Postnatally, the female secondary outgrowth remains small and develops into the clitoral gland, whereas the male counterpart differentiates into the larger preputial gland (Cunha 1975). To our knowledge, three mouse models have been described with developmental abnormalities of the preputial gland, namely the X-linked Tabby (Ta) and testicular feminization (Tfm) mutations (Drews 1975), and a Hoxd13 (Spdh) mutant (Johnson et al 1998).…”
Section: Absence Of Preputial Glands In Apcmentioning
confidence: 99%
“…Later on, the male gland develops faster under the influence of testosterone. Postnatally, the female secondary outgrowth remains small and develops into the clitoral gland, whereas the male counterpart differentiates into the larger preputial gland (Cunha 1975). To our knowledge, three mouse models have been described with developmental abnormalities of the preputial gland, namely the X-linked Tabby (Ta) and testicular feminization (Tfm) mutations (Drews 1975), and a Hoxd13 (Spdh) mutant (Johnson et al 1998).…”
Section: Absence Of Preputial Glands In Apcmentioning
confidence: 99%
“…2C). Laterally, in the proximal GT, two mesenchymal preputial swellings appear that enclose the preputial glands, epithelial glands seen from E13.5 (Cunha, 1975;Seifert et al, 2008). The PHUR epithelium remains in contact with the surface ectoderm of the ventral GT.…”
Section: Introductionmentioning
confidence: 99%
“…Development of the genital tubercle can be recognized at~E11.75 in the mouse (Perriton et al, 2002), and shortly thereafter the urethral plate can be observed in both male and female genital tubercles (Hynes and Fraher, 2004a, b;Petiot et al, 2005;Seifert et al, 2008;Yamada et al, 2006). Bilateral preputial swellings can be recognized extending laterally from the mouse genital tubercle at E14 (Cunha, 1975;Perriton et al, 2002;Petiot et al, 2005). It is perhaps worth noting that the preputial swellings of the mouse do not have a counterpart in humans.…”
Section: Discussionmentioning
confidence: 99%
“…9C and D). Preputial gland ducts arise at E14-E15 from the distal surface of the preputial swellings (Cunha, 1975) (see also Fig. 5).…”
Section: Figmentioning
confidence: 99%